Energy Efficiency Study at a Softwood Kraft Pulp Mill - Pedersén, Alexandra; Larsson, Anton (My University, 2017)
In order to achieve an increased energy efficiency within the Swedish industry the law about energy auditing in large companies has recently been implemented. The law is based on the EU Energy Efficiency Directive. The law requires that affected companies performs an energy auditing every fourth year. Besides mapping of energy supply and consumption, an analysis is required to be performed where suggestions for energy efficiency measures and related cost estimations are to be included. The result must thereafter be reported to the Swedish Energy Agency. The pulp and paper industry accounts for more than 1/6 of Sweden’s total energy usage which indicates the importance to study this specific industry from an energy perspective. This since implementation of energy efficiency measures can potentially result in large energy savings which can eventually result in a reduced climate impact. Södra Cell Värö is a Softwood Kraft Pulp Mill which has recently experienced a large expansion and reconstruction. Energy efficiency measures, such as a new secondary heating system, were included to improve the heat recovery within the process. In this master’s thesis, an energy efficiency study has been performed in order to investigate whether additional measures can be implemented to save energy at the pulp mill. Pinch analysis was utilized as a method to determine the potential for energy savings of the process. The result of the analysis shows that it is theoretically possible to save 66.7 MW steam, which corresponds to 23 % of the total steam consumption at the pulp mill. However, to achieve these savings a maximum energy recovery network is required which is rarely applied in industry due to technical limitations and that it is not feasible from an economic perspective to achieve such a heat exchanger network. Retrofit suggestions were proposed that utilized an identified excess heat in terms of warm water, and moist air from the drying machine. By doing so, the energy efficiency in the existing heat exchanger network was improved resulting in 9.1 MW steam savings. By also utilizing heat from flue gases from the lime kiln and the bark boiler, it was shown that a total of 19.5 MW steam savings could be achieved. Furthermore, it was found that the saved steam could for example be utilized to generate additional green electricity in the newly installed condensing turbine which in turn would enable an increased delivery of electricity to the grid by 41 GWh/yr. Another alternative that was investigated was to save fuel in the form of bark by reducing the steam production of the bark boiler. The result shows that it would be possible to save 144 GWh/yr bark. The potential for the process to deliver an increased amount of district heating was investigated and the result indicates that the theoretically maximum heat load for district heating delivery is 33 MW after the suggested energy efficiency measures have been implemented.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering